Road to 5g - Amri, Muhammad Hariz Adrian; Suhaili, Muhammad Izzat Hanafi; Mohktar, Aishatul Illia; Mohd Nor Bakri, Nurulhuda; Mohamed Nazri, Nurul Norfatin; Halim, Siti Noormashetah; Nathan, Shelena Soosay (Penerbit UTHM, 2021)
In addition to transforming the landscape around us, developments in technology are still pushing the wireless sector to create the next generation of network technology. Over the introduction of 5G, there is a lot of buzz building that will facilitate the entire world through constant and pervasive connectivity that links everyone to everything, everywhere, anywhere, and anyway, regardless of mobile, service, network Geographical life, or. 5G would also prove to be a paradigm change of wide bandwidths, vast numbers of antennas, and extreme base station and system densities, including high carrier frequencies. We examine the possible beneficiaries of 5G in this paper and describe the use-cases where 5G can have an impact. We consider three major use-cases in particular: Vehicle-to-Everything (V2X) Messaging, Helicopters and Healthcare. With regards to these use-cases, we discuss and demonstrate the challenges and limitations of existing wireless technology and describe how 5G can solve such shortcomings. The open research issues were also described and the potential future directions for coping with those problems were presented.